Maternal perception about temperament and interaction with the infant - Dos Santos, Luiza MacHado; Chiodelli, Taís [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP] (Universidad CES, 2023)
The mother's perception of the infant's temperament can influence her interaction with the child, altering the communicative opportunities of the dyad. This study analyzed the perception of 44 mothers about the interaction with their infants, considering their temperament. Mothers answered a questionnaire and were divided into groups according to the child's temperament: easy and mild. Results showed that mothers of infants, regardless of temperament, were more involved in caring and less in stimulating them. Mothers of easy-tempered infants reported that they enjoyed children, playing with them, and were more patient. Mothers of mild-temperament infants identified more negative aspects in their interaction with infants and reported a greater diversity of strategies to calm them. Results provided information for developing programs to meet the needs of the dyads and promote healthy interactions.
Percepción materna sobre el temperamento y la interacción con su bebé
Percepção materna sobre temperamento e a interação com o bebê
Keywords: infants; mother perception; mother-child interaction; parent involvement; temperament